Spatial patterns in long-distance dispersal of Quercus ilex acorns by jays in a heterogeneous landscape (Ecography, 2003)
In this paper, I analyse the interaction between the holm-oak Quercus ilex, and one of its main dispersers, the European jay Garrulus glandarius, in an heterogeneous Mediterranean landscape. I quantify the spatial dispersal pattern of the seed shadow at two spatial scales, landscape (among patches) and microhabitat (within patches), by directly tracking the movement of seeds. Two main traits of the jay-mediated dispersal of holm-oak acorns across the landscape, the spatial pattern of dissemination and the distance from the source tree, are significantly and directly influenced by jay activity. Jays moved acorns nonrandomly, avoiding one main patch type of the study area to cache acorns, the shrubland-grasslands, and moving most of the acorns to pine stands, whether afforestation or open pinewoods. Within each patch type, jays had also a strong preference for caching acorns in some microhabitats, since>95% of the acorns dispersed by jays were cached beneath pines. The distance of holm-oak acorn dispersal was long in the study site, over 250 m, with some dispersals occurring up to 1 km from the source oaks. The shape of the dispersal kernel function fitted to the dispersal pattern produced by jays differed from those quantified for many other plant species. Jay-mediated dispersal had two components, one local and another produced by long-distance dispersal. Due to the heterogeneity of these Mediterranean environments, this difference in scale overlaps with a difference in habitat composition, short distances events resulting in dispersals within the same oak stands and long distance events resulting in dispersal outside of oak stands, usually to other vegetation units. Jay activity and movement pattern can have thus dramatic effects on both the local regeneration as well as the potential for regional spread of the holm-oak populations.